2012
DOI: 10.1103/physrevlett.109.146401
|View full text |Cite
|
Sign up to set email alerts
|

Strength of the Effective Coulomb Interaction at Metal and Insulator Surfaces

Abstract: The effective on-site Coulomb interaction (Hubbard U ) between localized electrons at crystal surfaces is expected to be enhanced due to the reduced coordination number and reduced subsequent screening. By means of first principles calculations employing the constrained random-phase approximation (cRPA) we show that this is indeed the case for simple metals and insulators but not necessarily for transition metals and insulators that exhibit pronounced surface states. In the latter case, the screening contribut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…In the case of the Cr(001) surface, the electronic structure effect dominates the volume effect, thus leading to a decrease of the surface interaction matrix elements with respect to the bulk value, as discussed in detail in Ref. [23]. We neglect all Coulomb-interaction terms besides density-density terms.…”
Section: B Lda+dmftmentioning
confidence: 99%
“…In the case of the Cr(001) surface, the electronic structure effect dominates the volume effect, thus leading to a decrease of the surface interaction matrix elements with respect to the bulk value, as discussed in detail in Ref. [23]. We neglect all Coulomb-interaction terms besides density-density terms.…”
Section: B Lda+dmftmentioning
confidence: 99%
“…However, it has been reported that the value of Hubbard U for an isolated atom is about three to five times larger than an atom in a bulk solid [9]. Similarly, the Hubbard U at metal and insulator surfaces was recently reported to be different from their bulk value due to the competition between surface state and effective band narrowing [10]. Although the LDA + U method has been used in a few works on strongly correlated clusters [11,12], no work on self-consistently determined U for a strongly correlated cluster has been reported thus far.…”
Section: Introductionmentioning
confidence: 99%
“…For the parameterization of the onsite Coulomb interaction the constrained random phase approximation results of Ref. 40 are used. In their work a slab of 10 layers is considered for which they found the following onsite Coulomb interactions U 1/10 = 3.44 eV, U 2/9 = 4.64 eV, In order to use the CTQMC results as a benchmark the Cr(001) surface is modelled in exactly the same way as in Ref.…”
Section: Computational Detailsmentioning
confidence: 99%